Protection of Population Life Activities and Action in the Process of Emergencies (Eurasian Research Bulletin, 2023)
The article describes the stages of formation of the system for protecting the population and territories from emergency situations, eliminating the consequences of emergency situations, the stages and processes of the implemented reforms related to its activity, as well as the issues of determining the prospects for the future improvement of the system.